Categorising and defining popular psychological terms used within the youth athlete talent development literature: a systematic review - Dohme, L.-C.; Backhouse, S.; Piggott, D.; Morgan, G. (International Review of Sport and Exercise Psychology, 2017)
Inconsistencies in the use and definition of psychological terms within the talent development literature have been identified. To advance the scientific field, the creation of a shared language is recommended. This review aimed to systematically (1) identify terms used in empirical studies to describe psychological components purported to facilitate athletes` development; (2) analyse the definition and meanings of these terms; and (3) group, label, and define terms into meaning clusters. A systematic review using a narrative approach to synthesise information was conducted. A comprehensive literature search of SPORTDiscus, PsycINFO, PsycARTICLES, and ERIC was completed in May 2015. In total, 21 empirical studies, published between 2002 and 2015, met the inclusion criteria and were included in the narrative synthesis. Thematic analysis was used to analyse the findings. Identified psychological terms were categorised as psychological skills or psychological characteristics. Psychological skills were defined as athletes` ability to use learned psychological strategies (e.g., self-talk) to regulate and facilitate the enhancement of psychological characteristics. Psychological characteristics were defined as predispositions that impact upon athlete development (e.g., self-confidence). Despite being relatively enduring and consistent across a range of situations, psychological characteristics can be regulated and enhanced through the use of psychological skills.